Functional Surfactants for Molecular Fishing, Capsule Creation, and Single-Cell Gene Expression - Chowdhury, Mohammad Suman; Zhang, Xingcai; Amini, Leila; Dey, Pradip; Singh, Abhishek Kumar; Faghani, Abbas; Schmueck‑Henneresse, Michael; Haag, Rainer (Nano-Micro Letters, 2021)
Creating a single surfactant that is open to manipulation, while maintaining its surface activity, robustness, and compatibility, to expand the landscape of surfactant-dependent assays is extremely challenging. We report an oxidation-responsive precursor with thioethers and multiple 1,2-diols for creating a variety of functional surfactants from one parent surfactant. Using these multifunctional surfactants, we stabilize microfluidics-generated aqueous droplets. The droplets encapsulate different components and immerse in a bioinert oil with distinct interfaces where an azide-bearing surfactant allow fishing of biomolecules from the droplets, aldehyde-bearing surfactant allow fabrication of microcapsules, and hydroxyl-bearing surfactants, with/without oxidized thioethers, allow monitoring of single-cell gene expression. Creating multifunctional surfactants poses opportunities for broad applications, including adsorption, bioanalytics, catalysis, formulations, coatings, and programmable subset of emulsions. Highlights: 1 We have demonstrated how to create a parent surfactant that is open to manipulation, while maintaining its surface activity, robustness, and compatibility, to expand the landscape of surfactant-dependent microfluidic-droplet-based assays. 2 To create a library of functional surfactants from the parent surfactant, an oxidation-responsive small building block with thioethers and multiple 1,2-diols was used as a head group, while a non-polar perfluoropolyether chain was used as a tail.